CLIMATE SOLUTIONS FOR DESIGNING FLEXIBLE HOUSING IN INTERIOR DESIGN - Fereshteh Karimieyvanaki (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Nowadays, housing has become one of the main needs and issues and the mass construction of residential units has become more important than ever due to the growing population and migration to cities. On the other hand, the construction of small residential units has increased day by day due to the high cost of land and housing.Therefore, flexible housing following climate change is needed to achieve biological goals. The question of the study is what are the factors affecting the flexibility of the interior space in terms of climate?This was a qualitative study in which appropriate frameworks were examined and defined using a descriptive-analytical approach.